Optimal Placement of the Î¼pMUs in Distribution Systems Using Hybrid Technique - Vedantham, L.M. (IEEE Computer Society, 2020)
Micro Phasor Measurement Units (Î¼PMUs) are high precision measurement units which provides real time synchrophasor data. Every power system network must be kept under constant observation to prevent from line outage, divergence in the lines, topological attacks or failures and unidentified faults. Optimal placement of Î¼PMUs in Distribution Networks (DN) is very essential for complete observability of the system. Since distribution grids are small, the distance between the generators and the loads creates losses and poor efficiency of the system. The primary focus of this paper is to study the IEEE 13, 34 and 37 distribution test systems by implementing a Hybrid Rational Random Walk (HRRW). The proposed method utilizes the smart meter measurements of Î¼PMUs with enhanced system observability to obtain the complete topological observability. Along with this, HRRW detects the faults with high convergence speed. The case studies are distinctively dealt using MATLAB. Â© 2020 IEEE.